From "Sad People on Bridges" to "Kidnap and Extortion": Understanding the Nature and Situational Characteristics of Hostage and Crisis Negotiator Deployments. (19th June 2018) - Grubb, Amy Rose; Brown, Sarah J.; Hall, Peter; Bowen, Erica
Abstract: Hostage and crisis negotiation is well established as a police tool, and there is a growing body of literature that provides academic insight into the phenomenon. Academics have developed a corpus of literature to explain the way negotiators operate or how they can resolve incidents successfully. Whilst research in this area has originated from various countries and addressed negotiation from a variety of perspectives, there is limited research that has focused specifically on negotiation from an Anglo‐centric perspective. This article presents the findings from a detailed academic examination of negotiator experiences in England, whereby semistructured interviews were conducted with 15 negotiators from nine forces. Analysis using grounded theory revealed 12 deployment categories, situated within a recurring context involving subjects experiencing personal, emotional, or psychological crisis. These categories can be used to enhance our understanding of negotiator deployment in England and are discussed with reference to the implications for negotiator training and practice.